Komunikasi, Sumber Daya Manusia, Sikap dan Struktur Birokrasi (Edward-III) dalam Pelayanan Haji di Halmahera Timur - Sayid Athfal Alauddin; Abdurrahman Kader; Darwin Abdul Radjak (Universitas Merdeka Malang, 2025)
This study analyzes Communication, Human Resources, Attitudes, and Bureaucratic Structure in applying Edward III’s public policy implementation model to hajj management in East Halmahera Regency. The research involved 15 informants: 5 from the Welfare Division of the Regional Secretariat and 10 from the Ministry of Religious Affairs and local hajj participants. Using a qualitative approach, findings show that policy implementation is “fairly good,” especially in communication and assistance. Human resources are professional, but limited internet access hampers information flow. Staff attitudes are positive in both administrative and technical services. However, frequent SOP changes reduce effectiveness as communities struggle to adapt. Despite this, organizers remain responsible and committed to their duties